PEMANFAATAN PUPUK ORGANIK CAIR DARI SAMPAH RUMAH TANGGA SEBAGAI ALTERNATIF PENGGANTI AB MIX DALAM PERKEBUNAN HIDROPONIK - ramadhan, maulana (Cocos Bio, 2022)
This study aims to determine whether Liquid Organic Fertilizer (POC) from household waste is feasible as an alternative to AB Mix in hydroponic plantations. This is a true experimental research and uses Kangkung (Ipomoea aquatica) as the sample. The research design uses RAK (Randomized Block Design) which consists of 5 treatments. The first treatment used AB Mix without POC as a control, the second treatment was POC with a concentration of 5%, the third treatment was POC with a concentration of 10%, the fourth treatment was POC with a concentration of 15% and the fifth treatment was POC with a concentration of 20%. Data were analyzed using analysis of variance (variance print) followed by the BNT test at a significance level of 5%. The results showed that there was a significant difference in each observation variable, including: stem height = 17.58; number of leaves = 6.75; rod diameter =2.5; and the number of shoots that grew = 4.33